Traces, resonances and lessons of the pedagogical movement in Colombia - Acevedo Tarazona, Álvaro (Universidad Pedagógica y Tecnológica de Colombia, 2013)
Much has been written about the decline of the institutions of modernity in the Western version. Besides the family and the nation-state, some contemporary thinkers have suggested that, with the emergence of information technology and communication, the School has given way in the secondary socialization. In this so-called irreversible crisis, educators would be diminished their role as mediators and trainers of new generations at both the epistemological and the principles and values involved in any educational process. In this framework, the intention of this article is to come closer the history of the Pedagogic Movement, a history little known both in the continent and in Colombia, and that relates to the experience of a generation of teachers who at the beginning of the eighties fought for re-defining his profession.